What is the social dimension of the European Green Deal? - Kruszyński, Kamil (W poszukiwaniu zielonego ładu, 2022)
The chapter presents the social determinants of the EGD, the extent of poverty and social exclusion as well as persistent social inequalities in the EU, which remain unnoticed in the strategy. The social aspect of the EGD is expressed by the concept of a “just transition”, pointing to the circumstances conducive to its implementation, as well as mitigating the effects of energy poverty. The Mechanism to Support a Just Transition in the European Union is also presented.